Knowledge and Compliance Toward Standard Precaution Among Health Care Workers at Bahria International Hospital Lahore, Pakistan - Ather, Humira; Khan, Asaf; Shabnum, Saima (International Journal of Social Sciences and Management, 2020)
Introduction: Standard precaution is a way to stop the spread of hospital acquired infection which may be in the form of blood, secretions, body waste, body fluids and mucous membrane that may contain contagious infectious agents. Healthcare workers are the persons who have the moral obligation to care for sick persons and improve their regaining health and attain excellent worth of treatment care. Therefore, health care providers should have proper knowledge and good practice to strictly adhere to standard precaution control infection. Aim: To determine the knowledge and compliance toward standard precaution among health care workers in Bahria international Hospital Lahore. Methodology: a descriptive cross sectional study design were used for this study with sample size of 180 participants which were randomly selected from the target population. Results: The association between knowledge and practice was assessed through chi square test with p value=0.05, after apply this test the p value found .000 which is significant association between knowledge and practice. Whereas regression test shows value of adjusted R² showing 60% (F=.141, p <.001) of variance caused by independent variable (knowledge) in dependent variable (practice). Hence, it is proved that there is a significant positive relationship between knowledge and practice. Conclusion: The current study concluded that adhering to standard precaution is very important for all health care workers to control hospital acquired infection. Study finding also show that majority of the healthcare workers have good knowledge regarding standard precautions but they have unsatisfactory compliance to prevent and control infection. Int. J. Soc. Sc. Manage. 7(1): 17-20